Effects of a hybrid micro/nanorod topography-modified titanium implant on adhesion and osteogenic differentiation in rat bone marrow mesenchymal stem cells - Zhang WJ (Dove Medical Press, 2013)
Wenjie Zhang,1,2,* Zihui Li,3,* Qingfeng Huang,1 Ling Xu,1 Jinhua Li,3 Yuqin Jin,1,2 Guifang Wang,1,2 Xuanyong Liu,2 Xinquan Jiang11Department of Prosthodontics, 2Oral Bioengineering Laboratory, Shanghai Research Institute of Stomatology, Ninth People’s Hospital Affiliated to Shanghai Jiao Tong University, School of Medicine, 3State Key Laboratory of High Performance Ceramics and Superfine Microstructure, Shanghai Institute of Ceramics, Chinese Academy of Sciences, Shanghai, China *These authors contributed equally to this workBackground and methods: Various methods have been used to modify titanium implant surfaces with the aim of achieving better osseointegration. In this study, we fabricated a clustered nanorod structure on an acid-etched, microstructured titanium plate surface using hydrogen peroxide. We also evaluated biofunctionalization of the hybrid micro/nanorod topography on rat bone marrow mesenchymal stem cells. Scanning electron microscopy and x-ray diffraction were used to investigate the surface topography and phase composition of the modified titanium plate. Rat bone marrow mesenchymal stem cells were cultured and seeded on the plate. The adhesion ability of the cells was then assayed by cell counting at one, 4, and 24 hours after cell seeding, and expression of adhesion-related protein integrin β1 was detected by immunofluorescence. In addition, a polymerase chain reaction assay, alkaline phosphatase and Alizarin Red S staining assays, and osteopontin and osteocalcin immunofluorescence analyses were used to evaluate the osteogenic differentiation behavior of the cells.Results: The hybrid micro/nanoscale texture formed on the titanium surface enhanced the initial adhesion activity of the rat bone marrow mesenchymal stem cells. Importantly, the hierarchical structure promoted osteogenic differentiation of these cells.Conclusion: This study suggests that a hybrid micro/nanorod topography on a titanium surface fabricated by treatment with hydrogen peroxide followed by acid etching might facilitate osseointegration of a titanium implant in vivo.Keywords: micro/nanotexture, nanorod, titanium surface, bone marrow mesenchymal stem cells, adhesion, osteogenic differentiation